Root cause analysis of grease motor failure and improvements for the wire drawing process in a metallurgical industry - Cardoso, Adryelle dos Santos; Fernandes, Bruno Souza; Damm, Djoille Denner (Brazilian Journal of Production Engineering, 2025)
This article sought to identify the root cause of the grease fitting motor failure problem in a metalworking company and propose intervention measures to improve productivity levels. The method used to collect data was to conduct a Brainstorming session with wire drawing operators, followed by the construction of a Cause-and-Effect Diagram, and the application of the 5 Whys method to obtain the root cause. The 5W2H was also applied to propose actions for the grease fitting motor failure problem and to define intervention measures to avoid other quality and maintenance problems. The main causes found were lack of training, inadequate lubrication and the use of inadequate equipment, in the labor, raw material and machine categories, respectively, with the root cause being the lack of employee training. To avoid the grease fitting motor failure, the cost of R 3,000.00 for one month for training, installation of a key and marking of the maximum soap level stands out. Therefore, the study in the company allows the use of machines and tools correctly and with a reduction in errors, increasing availability and efficiency, and can be replicated in other industries.